Public Perspectives on Health Insurance Services: A Literature Review - Muhammad Alwy Arifin; St. Rosmanely (Yayasan Sinergi Kawula Muda, 2024)
Health insurance plays a crucial role in enhancing access to healthcare, improving health outcomes, and providing financial protection against catastrophic health expenditures. Public perspectives on health insurance services are vital in shaping the effectiveness and acceptance of these systems. This literature review synthesizes research on public perceptions of health insurance, focusing on factors influencing trust, satisfaction, and enrolment. The review explores differences in perspectives across various demographic groups and geographic regions, highlighting the impact of health system performance, communication strategies, and socioeconomic factors on public attitudes. The findings underscore the need for inclusive, transparent, and responsive health insurance services that align with the public's expectations and needs.